2018
DOI: 10.1039/c8cc06423g
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected, photochemically induced activation of the tetrabutylammonium cation by hexachloroplatinate(iv)

Abstract: A dinuclear, butadiene-bridged complex, trans-μ2:η2,η2-1,3-butadiene-bis(trichloroplatinate(ii)) (1) was unexpectedly obtained on photolysis of acetone solutions of (NBu4)2[PtCl6].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This transmetallation step is accompanied by the appearance of a pale purple colour and the formation of very small amounts of elemental gold (the latter also being observed, again in tiny quantities, in the direct auration reported below). Previously, we have observed that reaction of [PtCl 4 ] 2− with [AuCl 4 ] − leads to almost quantitative formation of [PtCl 6 ] 2− and either [AuCl 2 ] − or Au 0 depending on the stoichiometry, 20 while Au I is formed exclusively starting from [PdCl 4 ] 2− . 21 That very small quantities of gold are recovered from two transformations suggests that an analogous redox reaction is not a major side reaction in these transformations.…”
mentioning
confidence: 99%
“…This transmetallation step is accompanied by the appearance of a pale purple colour and the formation of very small amounts of elemental gold (the latter also being observed, again in tiny quantities, in the direct auration reported below). Previously, we have observed that reaction of [PtCl 4 ] 2− with [AuCl 4 ] − leads to almost quantitative formation of [PtCl 6 ] 2− and either [AuCl 2 ] − or Au 0 depending on the stoichiometry, 20 while Au I is formed exclusively starting from [PdCl 4 ] 2− . 21 That very small quantities of gold are recovered from two transformations suggests that an analogous redox reaction is not a major side reaction in these transformations.…”
mentioning
confidence: 99%
“…Previously, we have observed that reactions of platinum(II) salts (in our case depending on the stoichiometry. 20 In this case, there was evidence (purple mirror) for the formation of some Au 0 but in rather low quantity, suggesting that redox is not a major side reaction.…”
mentioning
confidence: 79%
“…We were able to determine its structure with precision for the first time using single-crystal X-ray methods. 6 Prepared as its potassium salt many years ago, 7 its structure was proposed following a detailed study using infrared and Raman spectroscopy, 8 although a later crystallographic determination as its Me 3 EtN + salt provided very little information. 9 Thus, as shown in Figure 1, the butadiene is s-trans with an anti arrangement of the PtCl 3 − moieties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, recently, we reported the very unexpected preparation of the anion ( trans -μ 2 :η 2 ,η 2 -1,3-butadiene)­bis­(trichloroplatinate­(II)) (Figure ), formed via photolysis of solutions of [NBu 4 ] 2 [PtCl 6 ] through a Shilov-type mechanism coupled with a Hofmann elimination. We were able to determine its structure with precision for the first time using single-crystal X-ray methods . Prepared as its potassium salt many years ago, its structure was proposed following a detailed study using infrared and Raman spectroscopy, although a later crystallographic determination as its Me 3 EtN + salt provided very little information .…”
Section: Introductionmentioning
confidence: 99%